G206(P) Growth and healthcare utilisation in premature babies discharged on home oxygen. (12th March 2018) - Pang, R; Williams-Gunn, H; Sinha, A; Rughani, P; Hird, M; May, C
Abstract : Background: Premature infants with bronchopulmonary dysplasia (BPD) are a vulnerable group of babies. Home oxygen provision facilitates early discharge, with the aim of minimising disruption to family life, hopefully optimising growth and reducing the financial burden on the NHS. We carried out a study to evaluate the growth and healthcare utilisation after discharge. Method: Data was collected retrospectively from electronic patient records for infants born between 2011–2014, discharged on home oxygen and followed up in clinic until 2 years old. This was evaluated against a comparison group who did not need home oxygen, matched for gestation. Weight SD scores were calculated using LMS calculator for Microsoft Excel. Data was analysed using SPSS. Results: Thirty-six babies discharged with home oxygen were evaluated against a comparison group of 19 babies born between 22+6 weeks and 30 weeks gestation. Babies discharged on home oxygen were ventilated longer (Mean=25.1 days vs 11.4 days) and were discharged a month after the comparison group (mean discharge gestation 43.9 weeks vs 39 weeks). Babies discharged with home oxygen were smaller at birth (25th centile vs 43rd centile, p<0.05), but there was no statistical significant difference in their weight centiles from 28 days to 2 years corrected. Both groups show poor growth in the first 28 days on NICU but they regained their birth centile by 4 months corrected. There was no statistical significance between the groups in the number of babies needing at least one Accident and Emergency (A and E) attendance or in-patient admission in the first year. A and E attendances were relatively common but only half resulted in admissions and very few required PICU admission (n=6) in the first year. Conclusion: Although babies on home oxygen were smaller and spent a longer period of time on the ventilator, their weight were similar to their preterm peers from 28 days old with catch up growth by 4 months corrected. Home oxygen requirement did not appear to additionally impact upon the A and E attendances, but the frequency of attendance suggests that improving parent education and enhancing community support for discharged preterm infants might reduce the burden on acute paediatric hospital services.